Subscribe for the Industrial Worker. Foremost Exponent of Revolutkonary Industrial Unionism ... Pyramid of Capitalist System - Copyrighted 1911 by The International Pub. Co., Cleveland, Ohio (1911)
Bemerkungen: Nachdruck ca. 1975; Archivstempel unten rechts